WASTE MANAGEMENT AND THE RESPONSIBILITY OF WASTE PRODUCERS TO THE ENVIRONMENT - Bakhtiar, Amanda Octavieni (Communale Journal, 2025)
This article aims to explain the problems at Talang Gulo TPA (Final Processing Site). The research method we use in this journal is an empirical juridical method using field data that we obtained from research at Talang Gulo TPA, Jambi City. The research approaches we use are a statutory approach and a conceptual approach. In this approach we use statutory regulations as a reference for problems in waste management and with a conceptual approach we analyze related issues regarding the management of Talang Gulo TPA. The results of the literature review can be summarized as two important problems, namely: waste management and producer responsibility towards the environment. TPA as the end of the waste management chain receives a large load of waste, causing negative impacts. There are many areas for sorting waste carried out by Talang Gulo TPA, namely: distillation area, compost area, landfill area, and LTP (Leachate Treatment Plant) area. It can be concluded that solving waste problems that is not comprehensive from end to end and does not involve all parties is the main obstacle to sustainable waste management.